An organizational approach to reducing and preventing restraint and seclusion use with people with acquired brain injury - Huckshorn, Kevin Ann; LeBel, Janice; Jacobs, Harvey E (NeuroRehabilitation (Reading, Mass.), 2014)
Seclusion, restraint (S/R) and coercive practices are used across human service populations, settings, with people of all ages. Their use has been increasingly scrutinized by the public, federal government and the media. Alternatives, interventions, and organizational approaches to these forms of containment are now emerging and advancing practice. This article provides an overview of the work conducted to reduce the use of coercion restraint, seclusion and other invasive practices in behavioral health settings that often include the defacto admission of persons with Acquired Brain Injury (ABI). The article also examines treatment culture factors that can exacerbate behavior dysfunction and how to moderate such challenges to prevent the use of S/R procedures among people with ABI. Seclusion and restraint can be avoided and greatly reduced in settings serving people with ABI. When S/R use is recognized as an inadequate organizational response to harmful behavior that maintains patterns of aggression or harm, leadership-driven core strategies can be implemented to disrupt the behavioral sequence. The Six Core Strategies© provide a prevention based framework to anticipate challenge, intervene early, and analyze the factors that contribute to maintaining the cycle of violence if S/R is used.